Employer and employer association matters in Australia in 2018. (June 2019) - Thornthwaite, Louise; Sheldon, Peter
For employers and employer associations, 2018 was in part a year of submissions to government inquiries, the 4-yearly modern wage review and the minimum wage review. Issues of numerical flexibility, including casual work, the gig economy and labour hire, also consumed much attention. It was also a year in which public discontent with the business world, particularly with big business, in relation to industrial relations and broader socio-political issues, and the questioning of its social licence to operate have escalated. In examining the major issues that concerned employers and their associations during the year, this article also discusses the pressures building for them in expressing and promoting their industrial relations agendas in response to a looming federal election, dynamic trade union campaigning and growing public discontent with the industrial relations system in its current form.